Gender Construction of Traditional Marriage at Sikka Krowe Ethnic - Nasa, Rikardus; Mayaputri, Velmi; Suswandari, Suswandari (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
Gender discrimination remains a contentious issue in Indonesian society. A misunderstanding of gender equality is one of the main causes. The utilization of local wisdom as an effort to provide understanding and uphold gender equality is one effective option. This research aims to explore gender equality in one of the local wisdoms of the Sikka Krowe ethnic, specifically in the customary marriage rituals. This research is a type of qualitative study utilizing an ethnographic approach. Data collection in this research utilizes interview and documentation techniques. The results of this research show that the traditional marriage rituals of the Sikka Krowe ethnic uphold gender equality in community life. Men and women in their roles as husband and wife in a household have complementary roles. The attitude of mutual respect is also emphasized in the customary expressions within the belis ritual. Thus, the ritual is very worthy of being preserved by the Sikka Krowe ethnic from one generation to the next.